Rehabilitation as a Disability Equality Issue A Conceptual Shift for Disability Studies? - Shakespeare, Tom 1966-; Cooper, Harriet; Bezmez, Dikmen; Poland, Fiona (2018)
Rehabilitation is a controversial subject in disability studies, often discussed in terms of oppression, normalisation, and unwanted intrusion. While there may be good reasons for positioning rehabilitation in this way, this has also meant that, as a lived experience, it is under-researched and neglected in disabilities literature, as we show by surveying leading disability studies journals. With some notable exceptions, rehabilitation research has remained the preserve of the rehabilitation sciences, and such studies have rarely included the voices of disabled people themselves, as we also demonstrate by surveying a cross-section of rehabilitation science literature. Next, drawing on new research, we argue for reframing access to rehabilitation as a disability equality issue. Through in-depth discussion of two case studies, we demonstrate that rehabilitation can be a tool for inclusion and for supporting an equal life. Indeed, we contend that rehabilitation merits disability researchers’ sustained engagement, precisely to ensure that a ‘right-based rehabilitation’ policy and practice can be developed, which is not oppressive, but reflects the views and experiences of the disabled people who rehabilitation should serve.
Keywords: Concept; Disability; Equality; Rehabilitation; Rights